Atypical Presentation of Wilson Disease without Kayser-Fleischer Ring in Geriatric Age - Anil Kumar T; Sudhir U; Priya Singal; Punith K (Al Ameen Medical College, 2010)
It is a rare event for Wilson Disease to have onset in geriatric age with neurological symptoms. And it is even rarer for such a condition to occur in the absence of Kayser-Fleischer Ring. We present a case of 63 year male who present with neurological symptoms of Wilson Disease without Kayser-Fleischer Ring which was confirmed by raised urine copper levels and Magnetic Resonance Imaging features classical of Wilson Disease